Effect of a multidisciplinary approach on hospital visit continuation in the treatment of patients with alcohol dependence - Tsutomu Kurata; Tasuku Hashimoto; Hitoshi Suzuki; Minoru Ishige; Shuichi Kikuchi (Neuropsychopharmacology Reports, 2023)
Abstract Aims Given the high dropout rates from initial treatment for alcoholism among patients with alcohol dependence, it is highly essential to prevent alcohol‐dependent patients from early dropout. This study aims to investigate whether a multidisciplinary approach can help achieve continuous hospital visits for this patient population for initial treatment. Methods This is a retrospective cohort study based on the medical records of all sequential alcohol‐dependent outpatients who visited Sodegaura Satsukidai Hospital for alcoholism at least once between October 2017 and March 2019. The primary outcome was the difference in the rates of patients who achieved 6 and 12 months of continuous hospital visits following the first visit with and without the multidisciplinary approach. Results Of all the participants (n = 67), the female‐to‐male ratios for patients supported with and without the multidisciplinary approach were 6:30 and 5:26, respectively. It was found that the rate of alcoholic patients treated with the multidisciplinary approach (n = 33, 91.7%), who had continuous hospital visits, was significantly higher than that of those without (n = 12, 38.7%) (χ2 = 21.2, p < 0.0001) during the first 6 months of treatment. Similarly, the rate of alcoholic patients treated with the multidisciplinary approach (n = 29, 90.6%) having continuous visits was significantly higher than that of those who did not receive such support (n = 8, 25.8%) (χ2 = 27.3, p < 0.0001) during the first 12 months. Conclusion A multidisciplinary approach can be used to reduce dropout from initial treatment among outpatients with alcohol dependence.